The Influence of Moist Wound Healing on the Condition of Wounds in Patients with Diabetic Ulcers - Alfian Alfian; Laily Widya Astuti (INDOGENIUS, 2026)
Background & Objective: Diabetic ulcers are a serious complication of diabetes requiring appropriate wound management to accelerate healing and prevent further complications. This study aims to determine the effect of the moist wound healing method on wound conditions in patients with diabetic ulcers. Method: A quasi-experimental design with a pretest-posttest one-group approach was used. Twelve diabetic ulcer patients were selected purposively. Wound conditions were observed directly on the first and seventh days after treatment using the moist wound healing method. Data were analyzed with a paired t-test to compare wound conditions before and after intervention. Result: There was a significant decrease in wound size (mean from 15.5 ± 0.45 cm² to 10.2 ± 0.53 cm²), wound depth, amount of exudate, and type of necrotic tissue. Granulation tissue increased significantly (mean from 1.6 ± 0.07 to 3.4 ± 0.07), indicating improved wound healing. Conclusion: The moist wound healing method significantly improves the wound condition in diabetic ulcer patients by accelerating healing, reducing wound size, exudate, and necrotic tissue, and promoting granulation tissue formation. This method is recommended as an effective therapy for managing diabetic ulcers.